Lennox-Gastaut syndrome and its impact on quality of life: hearing and speech perspective - Zizlavsky, Semiramis; Putri, Shally Adhina Adhina; Pamungkas, Indra Parmaditya; Anam, Khoirul; Mangunatmadja, Irawan (PERHATI-KL, 2022)
ABSTRACTBackground: Lennox-Gastaut syndrome (LGS) is a severe pediatric epilepsy syndrome characterized by multiple seizure types including tonic, atonic, atypical absence, and generalized tonic-clonic seizures. LGS is also associated with cognitive decline and various neural disturbance, including hearing loss. Purpose: To report a case of Lennox-Gastaut syndrome with unilateral hearing loss and delayed speech. Case report: Four years old boy with LGS and delayed speech was referred to the Otolaryngology Outpatient Clinic, Dr Cipto Mangunkusumo Hospital for hearing and speech ability evaluation. He had had repeated seizures since he was three weeks old, and also had cortical lesion and mild atrophy in the left hemisphere brain. Hearing tests with Otoacoustic Emission (OAE), Brainstem Evoked Response Audiometry (BERA), and Auditory Steady State Response (ASSR) revealed profound unilateral hearing loss in the left ear, which required hearing aid and also speech therapy. Clinical question: Is there any correlation between brain abnormality/damage with unilateral hearing loss and delayed speech in Lennox-Gastaut syndrome? Method: Using Pubmed, Proquest Database, and Hand Searching to search the evidence. The evidence selected will be appraised by at least two members of our group using Oxford Center of Evidence-Based Medicine (CEBM) worksheet. Result: Following screening of double publication and its suitability to our clinical questions over ten years, no literature was found. Conclusion: The patient was given antiepileptic drugs (AEDs) and postural control training. For the hearing and speech problems, as the best comprehensive treatment the patient was suggested to use hearing aids and undergo speech therapy program. ABSTRAKLatar belakang: Lennox-Gastaut syndrome (LGS) adalah kumpulan gejala epilepsi berat pada anak dengan ciri khas kejang multipel, tonik, atonik, kejang absans atipik dan tonik klonik menyeluruh. LGS juga berkaitan dengan penurunan kognitif dan berbagai gangguan saraf, termasuk gangguan pendengaran. Tujuan: melaporkan kasus sindrom Lennox-Gastaut dengan gangguan pendengaran satu sisi dan keterlambatan bicara. Laporan Kasus: Seorang anak laki-laki berusia 4 tahun dengan sindroma Lennox-Gastaut mengalami keterlambatan bicara dirujuk ke Departemen Telinga Hidung Tenggorok, Rumah Sakit Dr.Cipto Mangunkusumo untuk evaluasi ambang dengar dan penanganannya. Riwayat penyakit menunjukkan kejang berulang sejak berusia tiga minggu, yang ditemukan juga lesi di korteks serebri dan atrofi ringan pada hemisfer otak kiri. Berdasarkan Otoacoustic Emission (OAE), Brainstem Evoked Response Audiometry (BERA), dan Auditory Steady State Response (ASSR) ditemukan adanya gangguan pendengaran sangat berat unilateral pada telinga kiri dan membutuhkan Alat Bantu Dengar dan terapi wicara. Pertanyaan klinis:Apakah terdapat korelasi antara abnormalitas otak atau kerusakan otak dengan gangguan pendengaran unilateral dan keterlambatan bicara pada LGS? Metode: Pencarian bukti dilakukan melalui PubMed, Proquest, dan pencarian manual. Artikel yang didapatkan kemudian ditelaah oleh setidaknya dua anggota kelompok dengan menggunakan lembar kerja yang diperoleh dari Oxford Center of Evidence-Based Medicine (CEBM) Hasil: Setelah dilakukan skrining publikasi ganda dan kesesuaian dengan pertanyaan klinis dari sepuluh tahun terakhir tidak ditemukan literatur yang sesuai. Kesimpulan: Pasien ditangani dengan obat antiepilepsi dan latihan psikomotorik. Untuk gangguan pendengaran pasien dianjurkan untuk menggunakan Alat bantu Dengar dan terapi wicara. Penanganan kasus LGS harus menyeluruh untuk memperoleh hasil yang baik.